Magnon contribution to the magnetoresistance of iron nanowires deposited using pulsed electrodeposition - Sergelius, Philip; Moreno, Josep M. Montero; Waleczek, Martin; Boehnert, Tim; Goerlitz, Detlef; Nielsch, Kornelius (Physica Status Solidi-Rapid Research Letters, 2015)
Iron nanowires with a square cross section are grown by pulsed electrodeposition within a newly developed nanochannel template that allows for easy characterization. Measurements of the magnetoresistance as a function of magnetic field and temperature are performed within a large parameter window allowing for the investigation of the magnonic contribution to the magnetoresistance of electrodeposited iron nanowires. Values for the temperature dependent magnon stiffness D (T) are extracted: D (T) = D0(1 - d1T2) = 365(1 - 4.4 × 10-6 · T2 · K-2) meV Å2.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Electrodeposition; Iron nanowires; Magnetoresistance; Magnons; Nanochannels; Stiffness